Maximising Value on the Sale of a Business - Gray, Peter (London : Thorogood Herndon : Stylus Publishing, LLC [Distributor], 1999)
Annotation After getting married, moving house and starting a new job, selling a business is high up there with the most stressful things you can undertake. As a proprietor of a privately owned company every effort needs to be made to minimise the risks and maximise the buyer's offer. This is THE definitive A-Z guide on selling a business which splits the process down into two key stages. The 'pre-sale period' section of the Report examines what you hope to achieve when selling, looks at the most appropriate exit route to take and provides advice on appointing the best financial, legal and tax advisors. Part two is on the 'sale process' and concentrates on writing an information memorandum, identifying the optimal purchaser who is likely to pay the premium price and the negotiation itself (when effective due diligence and preparing legal contracts are the important issues). This Report is packed full of checklists, timetables, diagrams and jargon-free advice to make selling your business a more manageable project and a financial success!